Optimization Steam Time Human Hair Wate To Improve Plant Media Quality and Growth Of Leaf-Lettuce Plant (Lactuca sativa L.) - - (10612019), Widiyanti
Human hair waste steamed at 121Ã‚Â°C, 1,5 atm for 45 and 90 minutes has been reported increasing growth media quality and leaf-lettuce plant (Lactuca sativa L.) growth compared with soil. However there was no significance difference between both steam times. The aim of this research is to evaluate optimum steam time of human hair waste between 45 and 90 minutes to increase growth media quality and leaf-lettuce plant growth. Leaf-lettuce was planted in polybag containing soil and hair with ratio 1:20 (total media was 3 kg soil per polybag). Treatment groups were TR (soil + hair), TRS 45 (soil + hair steamed for 45 minutes), TRS 60 (soil + hair steamed for 60 minutes), TRS 90 (soil + hair steamed for 90 minutes), and TRS 135 (soil + hair steamed for 135 minutes) with T (100% soil) and R (100% untreated hair) as control groups. This research was conducted for two successive planting seasons using the same growth media. Result analysis showed TR, TRS 45, TRS 60, TRS 90 and TRS 135 media increase in porosity, aeration and CEC value (9-12%, 17-22%, 4-13% respectively). However there was no significance difference compared with T control group. Among all treatments, TRS 135 porosity, aeration, and CEC has the highest value which was 66-76%, 20-29%, and 30-41% respectively. WHC and pH in all treatment groups decreased, 4-13% for WHC and 7,2 to 6,8 for pH. The decreasing WHC and pH observed was not statistically different compared with T control group. On the first planting, leaf-lettuce growth in treatment groups were not significant compared with T control group. On the second planting, leaf-lettuce planted on TRS 60 resulted the best growth comparing with other treatments, but lower than T control group. N and P content of growth media and plant tissue in all treatments increased although its increasing was not statistically significant compared with T control group. Generally, hair waste steamed for 135 minutes increased growth media quality while steaming for 60 minutes increased leaf-lettuce growth.